Serum levels of immunoglobulin and complement in UTI of patients caused by Proteus mirabilis and using AgNPs as antiswarming - Al Otraqchi, Kamal Ismael Bakr; Darogha, Suhaila Nafee; Ali, Beriwan Abdulqadir (Cellular and Molecular Biology, 2021)
The use of plant extracts represents a promising approach for the synthesis of silver nanoparticles (AgNPs). This study reports the low-cost, green synthesis of AgNPs using the extract of clove and black seeds. The biosynthesized AgNPs were confirmed and characterized by analysis of the spectroscopy profile of the UV-visible spectrophotometer. The purpose of the present study is to evaluate the inhibitory effect concentration (MIC) of AgNPs, clove, and black cumin seed extracts on the growth and swarming of P. mirabilis. Clinical isolates of P. mirabilis were isolated from patients suffering from urinary tract infections. Thirteen types of antibiotics were used in the present study to detect their ability to inhibit P. mirabilis’s resistance. Immunological findings included the determination of serum levels of IgG, IgM, IgA and complement protein C3 and C4. Results showed that IgG and IgA concentrations significantly increased (1311.13 ± 72.54 and 279 ± 21.31) respectively in UTI patients in comparison to the healthy control group which was 1089.88 ± 37.33 and 117.611 ± 4.19 respectively, While IgM concentrations were increased non significantly in UTI patients (153.331 ± 6.45) in comparison to healthy control (145.2 ± 13.49). Complement components C3 showed a significant increase in UTI patients with mean values of 125.95 ± 6.22 compared to the control group with mean values of 55.191 ± 9.64, while C4 showed statically non-significant among UTI patients in comparison with the control group (35.195 ± 2.34 and 34.371 ± 1.22) respectively.